Analysis of Islamic Health Service Standardization: Implications and Challenges - Astiwara, Endy Muhammad (GoAcademica Research & Publishing, 2025)
This study aims to analyze the standardization of Islamic healthcare services by exploring the implications and challenges faced in various countries. The research approach used is qualitative, with data collection methods through literature studies, policy document analysis, and in-depth interviews with experts and practitioners of Islamic healthcare services to obtain comprehensive data. Thematic analysis methods are applied to identify key themes such as the integration of Islamic principles, the standardization process, and obstacles that arise in its implementation. The research findings show that several countries have adopted Islamic healthcare standards such as halal certification for medical products and sharia-compliant medical procedures even though there is no universal standard that is accepted globally. Key challenges include regulatory inconsistencies, limited human resources, infrastructure gaps, and cultural variations in the application of Islamic values ​​in the healthcare environment. Opportunities for international collaboration are a promising path to developing more inclusive and globally recognized standards. Strengthening the role of certification bodies and religious authorities is also key in supporting the adoption of Islamic healthcare standards. This study emphasizes the need for a more comprehensive approach to ensure that Islamic healthcare services are aligned with global quality standards, while respecting religious and cultural values.